Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
first set up equation
x times y=xy
so
xy=-29
and
x+y=1
subtract x from both sides
y=1-x
subsitute 1-x for y in first equation
x(1-x)=-29
distribute
x-x^2=-29
add x^2 to both sides
x=-29+x^2
subtract x from both sides
0=x^2-x-29
so we can use the quadratic formula to solve for x if the equation=0 and it is in ax^2+bx+c form so
if
ax+bx+c=0 then x=[tex] \frac{ -b+/-\sqrt{b^2-4ac} }{2a} [/tex] that means x=[tex]\frac{ -b-\sqrt{b^2-4ac} }{2a}[/tex] or x=[tex] \frac{ -b-\sqrt{b^2-4ac} }{2a} [/tex] so
x^2-x-29
a=1
b=-1
c=-29
[tex]\frac{ -(-1)-\sqrt{-1^2-4(1)(-29)} }{2(1)}[/tex]=[tex]\frac{ +1-\sqrt{1^2-(-116)} }{2(1)}=\frac{ +1-\sqrt{1^2+116} }{2}=\frac{ +1-\sqrt{117} }{2}= \frac{1-10.816653826392}{2} = [tex] \frac{-9.816653826392}{2}= -4.908326913196[/tex]
the second number is
[tex]\frac{ -(-1)+\sqrt{-1^2-4(1)(-29)} }{2(1)}=\frac{ +1+\sqrt{1^2+(-116)} }{2(1)}=
\frac{1+10.816653826392}{2} = \frac{ +1+\sqrt{117} }{2}=
\frac{10.816653826392}{2}=5.908326913196[/tex]
the two numbers are
5.908326913196 and
-4.908326913196
x times y=xy
so
xy=-29
and
x+y=1
subtract x from both sides
y=1-x
subsitute 1-x for y in first equation
x(1-x)=-29
distribute
x-x^2=-29
add x^2 to both sides
x=-29+x^2
subtract x from both sides
0=x^2-x-29
so we can use the quadratic formula to solve for x if the equation=0 and it is in ax^2+bx+c form so
if
ax+bx+c=0 then x=[tex] \frac{ -b+/-\sqrt{b^2-4ac} }{2a} [/tex] that means x=[tex]\frac{ -b-\sqrt{b^2-4ac} }{2a}[/tex] or x=[tex] \frac{ -b-\sqrt{b^2-4ac} }{2a} [/tex] so
x^2-x-29
a=1
b=-1
c=-29
[tex]\frac{ -(-1)-\sqrt{-1^2-4(1)(-29)} }{2(1)}[/tex]=[tex]\frac{ +1-\sqrt{1^2-(-116)} }{2(1)}=\frac{ +1-\sqrt{1^2+116} }{2}=\frac{ +1-\sqrt{117} }{2}= \frac{1-10.816653826392}{2} = [tex] \frac{-9.816653826392}{2}= -4.908326913196[/tex]
the second number is
[tex]\frac{ -(-1)+\sqrt{-1^2-4(1)(-29)} }{2(1)}=\frac{ +1+\sqrt{1^2+(-116)} }{2(1)}=
\frac{1+10.816653826392}{2} = \frac{ +1+\sqrt{117} }{2}=
\frac{10.816653826392}{2}=5.908326913196[/tex]
the two numbers are
5.908326913196 and
-4.908326913196
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.